A rare translocation in a patient with adult type polycystic renal disease: 46,XX t(3;5) (p26 - Yüce, Hüseyin; Özbey, Ülkü; Güleç Ceylan, Gülay; Elvas, Halit (Turkiye Klinikleri, 2007)
Adult type polycystic renal disease (APKD) is an autosomal dominant disease with cardinal symptoms like renal cysts, liver cysts and intracranial aneurysms. The aim of this study was to do pedigree analysis on the inheritance model of this disease and to emphasize the genetic counselling process in APKD. The conventional cytogenetic analysis of the patient revealed a karyotype of 46,XX, t(3;5)(p26
Erişkin tipi polikistik böbrek hastasinda nadir görülen bir translokasyon: 46,XX t(3;5)(p26
Keywords: Autosomal dominant; Chromosome aberrations; Phenotype; Polycystic kidney